Cellular fate of a plant virus immunotherapy candidate - Anthony O. Omole; Jessica Fernanda Affonso de Oliveira; Lucas Sutorus; Sweta Karan; Zhongchao Zhao; Barry W. Neun; Edward Cedrone; Jeffrey D. Clogston; Jie Xu; Michael Sierk; Qingrong Chen; Daoud Meerzaman; et al. (Communications Biology)
Abstract Cowpea mosaic virus (CPMV) is a plant virus that is currently being developed for intratumoral immunotherapy. CPMV relieves the immune system from tumor-induced immunosuppression; reprograms the tumor microenvironment to an activated state whereby the treated and distant tumors are recognized and eradicated. Toward translational studies, we investigated the safety of CPMV, specifically addressing whether pathogenicity would be induced in mammalian cells. We show that murine macrophage immune cells recognize CPMV; however, there is no indication of de novo viral protein synthesis or RNA replication. Furthermore, we show that CPMV does not induce hemolysis, platelet aggregation and plasma coagulation amongst other assays in human blood and immune cells. Taken together, we anticipate that these results will reinforce the development of CPMV as an immunotherapeutic platform.